Analisis Pengaruh Rasio Camels terhadap Pertumbuhan Laba pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Hidayatullah Hidayatullah; Roby Febrianto (Bina Nusantara University, 2012)
This study aims to analyze the influence of CAMELS method of profit growth in banking companies listed on stock exchanges of Indonesia. The methodology this research is t use purposive sampling, namely by taking a sample of 20 from a total of 30 banking companies listed on the Indonesia Stock Exchange. The type of data used are secondary data. Secondary data were obtained in the form of documentation of routine financial statements issued annually by competent parties contained in the Indonesia Capital Market Directory (ICMD) and the official site www.idx.co.id. This study tested the effect of CAR, NPLs, NIM, BO / PO, LDR, and the reserve requirement on profit growth at banks listed on the Indonesia Stock Exchange. Techniques of data analysis in this study using multiple linear regression analysis. F test results indicate that the variable CAR, NPLs, NIM, BO / PO, LDR, and the reserve requirement is jointly significant effect on the variable income changes. While partially by t-test, indicates that the variable has positive and significant CAR, NPLs and no significant negative effect, NIM has positive and insignificant, BO / PO and a significant negative effect, LDR has positive and significant, negative effect and the reserve requirement no significant effect on bank profit growth. The results also showed an adjusted R2 value of 18.3%. The limitations of this study is the sample data and the year that is used relatively little. The results of this study is expected to be taken into consideration for management to predict the growth of bank earnings and improve overall performance by improving business efficiency and credit portfolio without ignoring the precautionary principle.